2019
DOI: 10.1021/acs.jpcb.9b02443
|View full text |Cite
|
Sign up to set email alerts
|

Protein/Ice Interaction: High-Resolution Synchrotron X-ray Diffraction Differentiates Pharmaceutical Proteins from Lysozyme

Abstract: Protein/ice interactions are investigated by a novel method based on measuring the characteristic features of X-ray diffraction (XRD) patterns of hexagonal ice (Ih). Aqueous solutions of four proteins and other solutes are studied using high-resolution synchrotron XRD. Two pharmaceutical proteins, recombinant human albumin and monoclonal antibody (both at 100 mg/mL), have a pronounced effect on the properties of ice crystals, reducing the size of the Ih crystalline domains and increasing the microstrain. Lysoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…While it was first thought that adsorption onto the ice surface may be key for destabilization, 14 , 18 recent experimental and simulation results indicate that direct interaction with the interface is not needed. 19 23 In contrast, pressure build-up, 21 concentration gradients and pH shifts, 21 accumulation of gas bubbles, 24 , 25 or cold denaturation phenomena 22 were proposed as possible routes of denaturation upon ice formation. The addition of excipients to the protein formulation is therefore needed to prevent undesired loss of therapeutic potency and preserve the monomeric native conformation of the protein during both production and storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it was first thought that adsorption onto the ice surface may be key for destabilization, 14 , 18 recent experimental and simulation results indicate that direct interaction with the interface is not needed. 19 23 In contrast, pressure build-up, 21 concentration gradients and pH shifts, 21 accumulation of gas bubbles, 24 , 25 or cold denaturation phenomena 22 were proposed as possible routes of denaturation upon ice formation. The addition of excipients to the protein formulation is therefore needed to prevent undesired loss of therapeutic potency and preserve the monomeric native conformation of the protein during both production and storage.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a large air–water surface during mixing and shaking has often been shown to promote unfolding and aggregation. It is generally believed that the migration of proteins to the interface with air, as well as oil–water interfaces, where the exposure of the hydrophobic core is promoted, is responsible for the observed loss of stability. The formation of ice during freezing has also been found to be detrimental for proteins, but in this case, there still is no widespread agreement in the literature about the underlying mechanism. While it was first thought that adsorption onto the ice surface may be key for destabilization, , recent experimental and simulation results indicate that direct interaction with the interface is not needed. In contrast, pressure build-up, concentration gradients and pH shifts, accumulation of gas bubbles, , or cold denaturation phenomena were proposed as possible routes of denaturation upon ice formation. The addition of excipients to the protein formulation is therefore needed to prevent undesired loss of therapeutic potency and preserve the monomeric native conformation of the protein during both production and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Above this temperature, according to NMR measurements, no direct interaction is possible between the protein and the ice surface. More recently, X-ray diffraction studies of protein/ice interaction further suggested that two common pharmaceutical proteins, recombinant human albumin and a monoclonal antibody, interacted with ice crystals indirectly, by accumulating in the liquid-like layer above the ice surface, rather than by direct adsorption. Smaller protein molecules, such as lysozyme, were found to partition even further from the ice interface, in line with our simulations.…”
Section: Resultsmentioning
confidence: 54%
“…78 Separately, a high-pressure form of ice, tentatively identified as either IceIII or IceIX, has been recently reported to coexist with hexagonal ice in frozen solutions of proteins at 100 K (À173 C). 79 Both IceIII and IceIX would require pressures exceeding 2 kBar. It has been proposed therefore that, while the macroscopic sample environment was 1 Bar (i.e., atmospheric ambient pressure), the elevated pressures have been achieved due to freeze-induced volume expansion.…”
Section: Dpizkbdvi=vimentioning
confidence: 99%
“…87 Strain on the microscopic scale (microstrain) was recently measured in ice crystals during freezing of typical pharmaceutical solutions using high-resolution synchrotron X-ray diffraction. 79 Impact of different solutes, including several proteins and small molecular weight solutes, on the strain in ice crystals was evaluated on the microscale. A higher strain level was observed in the presence of mAb and human serum albumin, as compared to other solutes studied.…”
Section: Experimental Measurements Of Mechanical Stress During Freezingmentioning
confidence: 99%